2004
DOI: 10.1128/iai.72.10.5638-5645.2004
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa relA Contributes to Virulence in Drosophila melanogaster

Abstract: The stringent response is a mechanism by which bacteria adapt to nutritional deficiencies through the production of the guanine nucleotides ppGpp and pppGpp, produced by the RelA enzyme. We investigated the role of the relA gene in the ability of an extracellular pathogen, Pseudomonas aeruginosa, to cause infection. Strains lacking the relA gene were created from the prototypical laboratory strain PAO1 as well as the mucoid cystic fibrosis isolate 6106, which lacks functional quorum-sensing systems. The absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(132 citation statements)
references
References 54 publications
8
122
1
1
Order By: Relevance
“…In this study, we have confirmed the role of FTN_1518 in F. novicida U112 as a (p)ppGpp synthetase, and demonstrated that disruption of this gene results in abolition of ppGpp production under conditions of amino acid starvation. This is similar to the situation in Pseudomonas aeruginosa (Erickson et al, 2004) and V. cholerae (Haralalka et al, 2003), in which mutation of the relA gene alone results in reduced (p)ppGpp accumulation. Unlike other organisms such as E. coli, in which both relA and spoT genes need to be inactivated (Xiao et al, 1991), RelA alone appears to be required for (p)ppGpp synthesis in F. novicida during amino acid starvation.…”
Section: Discussionsupporting
confidence: 62%
“…In this study, we have confirmed the role of FTN_1518 in F. novicida U112 as a (p)ppGpp synthetase, and demonstrated that disruption of this gene results in abolition of ppGpp production under conditions of amino acid starvation. This is similar to the situation in Pseudomonas aeruginosa (Erickson et al, 2004) and V. cholerae (Haralalka et al, 2003), in which mutation of the relA gene alone results in reduced (p)ppGpp accumulation. Unlike other organisms such as E. coli, in which both relA and spoT genes need to be inactivated (Xiao et al, 1991), RelA alone appears to be required for (p)ppGpp synthesis in F. novicida during amino acid starvation.…”
Section: Discussionsupporting
confidence: 62%
“…Larvae of G. mellonella have been used previously to distinguish between Aspergillus species producing different levels of the immunosuppressive agent gliotoxin [7] and insects have also been used to quantify the role of rel A gene in contributing to the virulence of P. aeruginosa [16] and the virulence of mutants of A. fumigatus lacking the nucleolar protein Cgr A [11]. There is increasing attention being focused on the use of insects for measuring changes in microbial virulence -a process which has time and cost benefits to the researcher as well as ethical benefits in reducing the need to use mammals for this form of testing [3].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the ability of bacteria to synthesize (p)ppGpp and mount a stringent response is an essential physiological adaptation required for stages of pathogenesis, such as initial growth of adherent bacteria [38], toxin production [39], motility [40] and expression of other virulence regulators [41]. Comparative analysis revealed that the IPAV spoT gene (LIF_A2491) has two missense mutations at the amino-acid residues, Val293 and Lys407, resulting in replacement by Ala and Glu, respectively.…”
Section: Mutations Affecting Genes Related To Stress Responsementioning
confidence: 99%